Potential Adverse Effects of Creatine Supplement on the Kidney in Athletes and Bodybuilders (Iranian Journal of Kidney Diseases, 2018)
Introduction. Nowadays, creatine is one of the most common oral supplements used by professional athletes for boosting their strength and muscle mass. In this review, we collect available experimental and clinical data about renal safety of both short-term and long-term use of creatine. Materials and Methods. Scientific literature was critically searched by keywords "creatine," "renal insufficiency," and "renal dysfunction" and their synonyms in medical databases (Scopus, MEDLINE, EMBase, and ISI Web of Knowledge). Overall, 19 relevant clinical and experimental articles were selected for this review. Results. Short- and long-term creatine supplementations (range, 5 days to 5 years) with different doses (range, 5 g/d to 30 g/d) had no known significant effects on different studied indexes of kidney function such as glomerular filtration rate at least in healthy athletes and bodybuilders with no underlying kidney diseases. In addition, although short-term (range, 5 days to 2 weeks) high-dose oral creatine supplementation (range, 20 g/d to 0.3 g/kg/d) stimulated the production of methylamine and formaldehyde (as potential cytotoxic metabolites of creatine) in the urine of healthy humans, there was currently no definite clinical evidence about their adverse effects on the kidney function. Conclusions. Although creatine supplementation appears to have no detrimental effects on kidney function of individuals without underlying kidney diseases, it seems more advisable to suggest that creatine supplementation not to be used by sportsmen or women with pre-existing kidney disease or those with a potential risk for kidney dysfunction.